Marriage exchanges, seed exchanges, and the dynamics of manioc diversity - Delêtre, Marc (National Academy of Sciences, 2011)
The conservation of crop genetic resources requires understanding the different variables—cultural, social, and economic—that impinge on crop diversity. In small-scale farming systems, seed exchanges represent a key mechanism in the dynamics of crop genetic diversity, and analyzing the rules that structure social networks of seed exchange between farmer communities can help decipher patterns of crop genetic diversity. Using a combination of ethnobotanical and molecular genetic approaches, we investigated the relationships between regional patterns of manioc genetic diversity in Gabon and local networks of seed exchange. Spatially explicit Bayesian clustering methods showed that geographical discontinuities of manioc genetic diversity mirror major ethnolinguistic boundaries, with a southern matrilineal domain characterized by high levels of varietal diversity and a northern patrilineal domain characterized by low varietal diversity. Borrowing concepts from anthropology—kinship, bridewealth, and filiation—we analyzed the relationships between marriage exchanges and seed exchange networks in patrilineal and matrilineal societies. We demonstrate that, by defining marriage prohibitions, kinship systems structure social networks of exchange between farmer communities and influence the movement of seeds in metapopulations, shaping crop diversity at local and regional levels.